Carbon supported size-controlled ru catalysts for selective levulinic acid hydrogenation into γ-valerolactone - Simakova, Irina L.; Demidova, Yuliya S.; Simonov, Mikhail N.; Niphadkar, Prashant S.; Bokade, Vijay V.; Devi, Nandini; Dhepe, Paresh L.; Murzin, Dmitry Yu (Journal of Siberian Federal University-Chemistry, 2020)
Liquid phase levulinic acid hydrogenation into γ-valerolactone in 1,4-dioxane as a solvent (165°C, 20 bar) was studied over a range of Ru monometallic catalysts using mesoporous carbon material Sibunit as a support. In addition to the catalyst prepared by impregnation with RuCl3∙nH2O (0.1 M) followed by reduction in H2, size-controlled Ru(NPs)/Sibunit catalysts were synthesized by immobilization of polyvinylpyrrolidone (PVP) stabilized Ru nanoparticles (NPs) (dRu=2.4 nm). Сarbon supported colloidal Ru NPs were not studied earlier in levulinic acid hydrogenation. Activity of colloidal Ru(NPs)/Sibunit catalysts was found to be lower than that of impregnated Ru/Sibunit which could be attributed to hampering effect of PVP. However, colloidal Ru(NPs)/Sibunit purified by thermal treatment in air (180°C) followed by reduction in H2 (400°C) exhibited the same activity as impregnated one yielding 93% γ-valerolactone at 100% levulinic acid conversion. Applicability of supported PVP-assisted colloidal Ru NPs in hydrogenation of levulinic acid illustrates a potential to prepare more efficient catalysts for this reaction with a desired particle size. The catalysts were characterized by TEM, XRF, and N2 physisorption to compare their physical chemical properties.

Chitosan-derived carbon supported ruthenium catalyst for efficient hydrogenation of levulinic acid to γ-valerolactone - Korampattu, Lavanya; Dhepe, Paresh L. (Sustainable Energy & Fuels, 2025)
The transition from fossil fuels to sustainable energy and chemical production relies heavily on efficient biomass valorization. Levulinic acid (LA), a key platform chemical from lignocellulosic biomass, serves as a versatile precursor for valuable chemicals like gamma-valerolactone (GVL), a promising green solvent, fuel additive, and polymer precursor. While ruthenium-based catalysts are effective for LA hydrogenation, conventional systems like Ru/C often suffer from metal leaching and deactivation due to weak metal-support interactions. Current approaches to improve stability, such as using nitrogen-doped carbon supports, involve complex synthesis and synthetic nitrogen precursors. Addressing these limitations, we present a facile and sustainable strategy for synthesizing a robust ruthenium catalyst by directly pyrolyzing marine biomass-derived chitosan to form a self-nitrogen-doped carbon support. This catalyst exhibited superior stability and excellent recyclability in the aqueous-phase hydrogenation of LA to GVL, surpassing conventional Ru/C while maintaining activity comparable to that of leading Ru catalysts supported on N-doped carbon. Unlike other N-doped carbon supports, our method avoids synthetic N-dopants and tedious procedures, making it inherently more sustainable. Detailed characterization via XPS and H2-TPR revealed strong metal-support interactions, facilitated by intrinsic nitrogen functionalities, effectively stabilizing the ruthenium species. This study also identifies the critical role of graphitic and pyridinic nitrogen species in controlling catalytic activity and elucidates the importance of optimizing nitrogen species and content in tailoring chitosan-derived supports. The proposed mechanism describes how Ru-N centers activate hydrogen and LA, with basic nitrogen sites aiding the dehydration step to GVL. Overall, this work features the potential of chitosan derived carbon as a sustainable and tunable support for efficient biomass hydrogenation catalysts and offers fundamental insights into the role of nitrogen doping in tailoring catalytic performance.

Continuous flow hydrodeoxygenation of lignin-derived guaiacol to cyclohexanol over durable Al2O3 hollow fiber supported co catalyst - Singh, Dheerendra; Jogdand, Shunottara M.; Devi, R. Nandini; Dhepe, Paresh L. (ChemCatChem, 2025)
The drive to decarbonize the chemical, oil, and gas industries through use of bio-derived resources is intensifying. This study focuses on converting lignin-derived phenolic compounds into cyclohexanol, a precursor for adipic acid production. The alumina hollow fiber supported cobalt catalyst (5Co/AHF@capillary) prepared by capillary action method was found to consist cobalt in both metallic and +delta oxidation states. Initial tests in a batch-mode reactor showed promising results, with 5Co/AHF@capillary catalyst demonstrating catalytic activity comparable to Ru/Al2O3 systems (225 degrees C, 1 MPa H-2, 4 h), achieving similar to 86% cyclohexanol yield in guaiacol hydrodeoxygenation reactions. The catalytic system was then adapted for continuous flow reactors under milder conditions (300 degrees C, 2.5 MPa H-2, 18 mL min(-1)), resulting in 83% guaiacol conversion and 74% cyclohexanol yield. The durability of the catalyst was checked for >80 h and results claim that catalyst was active in yielding consistent results. The roles of catalyst preparation method, hydrogen pressure, solvent, WHSV were thoroughly checked and discussed.
Keywords: biomass valorization; Carbon; Co/Al2O3; Cyclohexanol; lignin